Rapid Assessment of Seabed Habitats Around Pitcairn Island in Aid of Activity Management During the COVID-19 Global Pandemic - Archer-Rand, Simeon; Whomersley, Paul; O’Connor, Joey; Dosell, Abbie (Frontiers in Marine Science, 2021)
The global COVID-19 pandemic of 2020 has forced small island states to make rapid changes to the way they manage their marine estates following changes in global shipping practices and access which are essential for the supply of food items and island’s infrastructure. Following the closure of the border of neighbouring French Polynesia, changes had to be made to the Pitcairn Islands’ sole supply vessel route, which resulted in the vessel requiring to set anchor on arrival at the island to conserve fuel. Considering this change and to ensure the continued protection of vulnerable coral habitats the local government has had to make swift decisions to identify anchoring zones that minimise seabed disturbance. Data collected in January 2020, just prior to the pandemic, were assessed using a rapid assessment method and combined with earth observation data to create the first shallow water (< 20 m) habitat map of this island. The results show the distribution of vulnerable coral communities and other habitats, achieving an accuracy of 68% compared with previously collected datasets making the results the best available evidence for management purposes. Although the seabed data were not originally collected for this analysis, having both video and stills imagery aligned with global positioning meant a rapid assessment method could be easily applied to the data. The assessment technique used has resulted in the first reliable habitat distribution maps to be produced in a management critical timeframe, providing managers with the evidence they required to make informed decisions relating to the protection and conservation of Pitcairn’s pristine, marine habitats during these unprecedented times.